FAULT TREE ANALYSIS DAN AUDIT AKURASI PADA PENERAPAN SISTEM MANAJEMEN KESELAMATAN KERJA KONSTRUKSI TERINTEGRASI Studi Kasus: Proyek Pembangunan Gedung Pelayanan (Fisik) RSUD Tidar Kota Magelang, Kontraktor B1 - Alvian Purbiantoro; Adwitya Bhaskara (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2020)
Building a construction project is an activity which contains many dangerous elements. It causes the construction industries have bad record in the terms of occupational safety. Therefore, occupational safety is an aspect that must be improved any time because it is a very complex problem which covers issues in the terms of humanity, legal aspect, accountability and the image of the organization itself. This study aims to (1) Determine the accuracy level of the Occupational Safety Management System Application in the Service Building (physical) Construction Project in Tidar Regional Hospital (RSUD) Magelang, (2) Identify and analyze the potential risks of work accident by using Fault Tree Analysis (FTA) method and planning mitigation to reduce the scope of construction in progress. This study is a quantitative analysis where the research is conducted by collecting the primary data through interview and observation, meanwhile the secondary data is in the form of data from the project itself. FTA is used to investigate the potential of workplace accidents by analyzing the direct causes to the basic causes of the accident itself. The results of the study show that (1) The accuracy level of the application of Occupational Safety Management System which has been applied has an assessment rate of 97.29% and it is included in the level of satisfactory assessment. (2) The results of the analysis using FTA obtained several incidents that potentially can cause workplace accidents, incidents such as the workers who do not wear personal protective equipment, workers who act carelessly, and the lack of work experience are the frequent cases in the basic FTA incidents.